Nursing Care Process at the Beginning of Professional Maturity: a Glance to from Chronic Diseases - Lázaro Roberto Herrera Fragoso; Lázaro Luis Hernández Vergel; Tania Chaviano Pérez (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Some professionals as consider implementing the Nursing Care Process: ¨the beginning of professional maturity¨. The nursing science is based in a wide theoretical framework. The Nursing Care Process is a method through which this framework is applied to practice. Its implementation has not achieved in correspondence to the knowledge that technicians and professionals have acquired. In some units of the National Health System in which this process is applied there are frequent difficulties in the already graduated personnel so as in the group in training. These difficulties are based mainly on the diverse exiting criteria and ideas, even among those professionals in charge of its teaching.